Disentangling spectral phases of interfering autoionizing states from attosecond interferometric measurements. Issue 7 (January 2020) - Petersson, C L M; Barreau, L; Klinker, M; Camper, A; Marante, C; Gorman, T; Kiesewetter, D; Argenti, L; Agostini, P; González-Vazques, J; DiMauro, L F; Salières, P; et al.
Synopsis: The spectral phase of the autoionising neon continuum has been probed via interferometric pump-probe measurements as well as ab initio, full-electron, time-dependent, theoretical calculations in energy intervals containing several auto-ionising. Theory and experiment are in excellent agreement. Despite the complex energy-dependence of the phase, a very simple model has been used to disentangle the contribution by different resonances. This work extends the applicability of reconstruction methods to multi-resonance regions of autoionising continua - a common scenario in multi-electron systems.